The Factors Impede Teachers’ Effective Use of Audio Visual Materials to Teach English Speaking Skills: ABBA PASCAL Girls’ School in Focus, Wolaita Zone, Southern Ethiopia - Amanuel Yonas; Senapathy M (Randwick International of Education and Linguistics Science Journal, 2020)
The purpose of this study was to explore factors impede teachers’ effective use of AVMs to teach ESS at Abba Pascal Girls’ School. The subjects used were 2 English teachers of grades 5, 6, 7 & 8 and sampled students. The grades had 2 sections that encompassed 50 students each. Convenience & systematic sampling techniques were employed to select the school & 32 informants among the population of 400. To get the exact number of the participants which are 4 of each section, the researchers divided the population’s number of the sections into the numbers of each student’s representation accordingly: 50÷4 = 12.5. Thus, every Nth participant was selected systematically according to their attendance lists. Therefore, 4 informants from each section were taken in the intention of the researchers. Both the teachers were directly taken as participants due to the manageable number of entire population. Then, the researchers employed mixed research approach after collecting data through questionnaire, interview & classroom observation. Quantitative data were analyzed in percentages; while qualitative were thematically organized & categorized in a statement form. Conclusion & recommendations were forwarded based on the findings. The findings are learning ESS using AVMs benefit teachers & students. Conversely, the challenges drawback teachers’ effective use of AVMs were underpinned in categories of, the challenges related to classroom, gadgets, teachers & students. Therefore, stakeholders of the school should facilitate technical training sessions for teachers & consider the class size. Finally, the windows of the classrooms should be painted with non-translucent paints.